Femoral fracture in congenital femoral deficiency.A therapeutic challenge? Femurfraktur bei kongenitalem Femurdefekt: Eine therapeutische Herausforderung? - Jungbluth, Pascal; Wild, M.; Miersch, D.; Windolf, J.; Hakimi, M.; Betsch, Marcel (Orthopäde, 2009)
There are no reports in the literature about femoral fractures in adults with congenital femoral deficiency. We report on a femoral fracture in a 60-year-old patient with congenital femoral deficiency.Despite early difficulties in mobilisation and delayed union after an angle-stable plate osteosynthesis, full weight bearing was reached after 8 months.The treatment of fractures in combination with congenital femoral deficiency remains difficult and depends on the extent of the defect, the complexity of the fracture, and associated anomalies.The objective of the often demanding operative treatment of a femoral fracture in combination with a congenital femoral deficiency should be reestablishment of the patient's walking ability. © Springer Medizin Verlag 2009.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Congenital femoral focal deficiency; Congenital short femur; Femoral fracture; Outcome; Therapy